Augustyna Wróblewskiegoo uwagi o pornografii - Antonów, Radosław (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Pornography at the turn of the nineteenth century was a significant social and moral problem, while its rise was indirectly linked to the growth of the criminal offences of human trafficking and prostitution. Discussion on the issue of pornography and its countermeasures has taken place in Polish political, cultural, and academic circles since the final years of nineteenth century. Augustyn Wróblewski, a chemist, social activist, and forerunner of Polish anarchism, took a stance on pornography, in particular with regard to its influence on art and culture. Although he did not conduct a thorough analysis of this phenomenon, in his articles Wróblewski explored the serious doubts harbored by researchers and commentators of phenomena exerting a negative social impact
Keywords: pornography; human traficking; prostitution